1984
DOI: 10.2134/agronj1984.00021962007600050020x
|View full text |Cite
|
Sign up to set email alerts
|

Steer Performance from Two Perennial PennisetumSpecies, Switchgrass, and a Fescue—‘Coastal’ Bermudagrass System1

Abstract: Subtropical perennial grasses make important contributions to productive, season-long grazing systems in the USA. The perennial bermudagrasses, particularly 'Coastal' bermudagrass (C}'nodon dac-t}'lon (L.) Pers.), are extremely productive, but high fiber allows only poor to moderate animal performance. Steer average daily gains (ADG) and productivity estimates of the subtropical perennials Oaccidgrass (Penni.retum flaccidum Griseb.), P. orientak Rich., and switchgrass (Panicum virgatum L.) were obtained. Sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
61
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 9 publications
(9 reference statements)
7
61
0
1
Order By: Relevance
“…At this stage, we found the harvested biomass to be 5.8% crude protein, 73.4% NDF, and 58.7% digestible dry matter on average across locations (Table 3). Crude protein concentrations below 7% of dry matter limit ruminal fermentation of forages and do not meet minimal protein requirements of growing animals (Burns et al 1984). Intake of forage also may be restricted at such high NDF concentrations (Ball et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, we found the harvested biomass to be 5.8% crude protein, 73.4% NDF, and 58.7% digestible dry matter on average across locations (Table 3). Crude protein concentrations below 7% of dry matter limit ruminal fermentation of forages and do not meet minimal protein requirements of growing animals (Burns et al 1984). Intake of forage also may be restricted at such high NDF concentrations (Ball et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its agronomic potential as a bioenergy feedstock crop, a number of studies report that grazing early growing switchgrass produces good beef cattle gain. For instance, Burns, Mochrie, and Timothy [16] reported that switchgrass pastures evaluated in North Carolina maintained a long growing season and had a valuable impact on average daily gain. Mosali et al [17] reported average daily gains ranging between 0.83 and 1.05 kg hd −1 for stocker cattle grazing between early April and late May.…”
Section: Introductionmentioning
confidence: 99%
“…Diferentes PP condicionam diferentes quantidades de MS/ha ou resíduo de MS aérea. Com a redução na PP tem-se maiores resíduos (BURNS et al, 1984;ESCOSTEGUY, 1990;MORAES, 1991). Esta condição afeta a taxa de crescimento da pastagem e sua conseqüente produção de MS (KORTE et al, 1987).…”
Section: Introductionunclassified